ANALISIS PERBANDINGAN VISI, MISI, TUJUAN, DAN PELAKSANAAN OPERASIONAL PAUD DI RA PLUS JA-ALHAQ, TK DHARMAWANITA, DAN PAUD HANGTUAH - Nasron, M.; Amelia S, Irfa Rizka; Silvia, Silvia; Ramadhani, Ambar Putri; Indri Oktaviani, Ningmas; Iskoriat, Yudas (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2025)
This study aims to compare the vision, mission, objectives, and operational implementation of early childhood education (PAUD) in three educational institutions, namely RA Plus Ja-alHaq, TK Dharmawanita, and PAUD Hangtuah. The focus of this study is to analyze the differences in approaches to character building for children, social development, and creativity-based learning in each institution. The method used in this study is qualitative research with a case study approach. Data collection was carried out through reports of observation results conducted in the three institutions. The results of the study show that although the three institutions have a vision that leads to the formation of children's character and intelligence, there are differences in the emphasis of educational aspects, both in terms of learning methods and operational activities carried out. RA Plus Ja-alHaq emphasizes religious education, while TK Dharmawanita and PAUD Hangtuah focus more on creativity and social skills. These results show the importance of diversity of approaches in PAUD education to achieve holistic child development